A methodology of design for affordances using affordance feature repositories. Issue 3 (28th July 2015) - Brown, David C.; Maier, Jonathan R.A.; Kim, Yong Se
Abstract People interact with artifacts, either products or services, in their lives. These interactions are based on two-way communication between people and artifacts. The characteristics of artifacts that induce natural activities of people, affordances, play critical roles in making interactions successful and meaningful. The notion of affordance features, structural elements of artifacts that provide affordances, has been proposed earlier. In this paper, a methodological framework for design for affordances is proposed where repositories of affordance features are used. Affordances are identified through function–task interaction matrices or use activity observations. Using an affordance feature repository where many alternative structural elements for a specific affordance are stored together with corresponding design constraints and contexts, affordance features for those identified affordances are retrieved considering similarities between the target design constraints and those of the affordance features in the repositories. Using the clues given by such affordance features, a new affordance feature is to be designed through analogical reasoning. We present this design for affordance framework together with illustrative cases where various designers designed affordance features using affordance feature repositories.